Virullent Newcastle disease virus differentially modulates chicken splenic lymphocyte/macrophage populations and cytokine expression. - Rasoli, Mehdi; Sheau, Wei Tan; Swee, Keong Yeap; Ideris, Aini; Bejo, Mohd Hair; Kaiser, Pete; Omar, Abdul Rahman
Newcastle Disease virus (NOV) is a highly infectious virus which contributed to the major causes of economic losses in poultry industry. Since 1960 the majority of virulent NOV circulating throughout the world are of genotypes V, VI, VII, VIII and X. Since 2000 until present, genotype VII is the predominant NOV strains circulating in various parts of the world. In addition, the majority of the outbreaks are reported in NOV vaccinated flocks. Studies have been carried out to determine the possible factors contributed to the ability of the virus to break vaccine-induced immunity. However, the interaction of virulent NOV with different lymphocytes is still unclear. Understanding the virus immunoregulation on the host immune system will provide valuable information to define the molecular immunopathology of the virus. In this study, we characterize the immunoregulation of virulent NOV genotype VII and VIII on chicken macrophages, Band T lymphocytes during the acute stage of the respective virus infection in specific-pathogen-free (SPF) chickens. Spleen T! B lymphocytes and macrophage population were quantified using flow cytometry while cytokines expression was quantified using both GenomeLab GeXP system and real-time PCR assay. Results have shown that NOV from genotype VII (lBS/002) and VIII (AF2240) induced drastic reduction of C04 and COS T lymphocyte associated with infiltration of macrophage in spleen day 3 post-infection. The depletion of the T lymphocytes is primarily through the process of apoptosis. Significant upregulation of pro-inflammatory and Th-1like cytokines such as IFN-y, IL-ll3, IL-6, IL-12a and IL-B expression was also observed in the spleen of NOV infected chicken after day 3 post-infection. However, no significant changes were detected on the expression of majority of Toll-like receptor(TLR) genes. The immunoregulation effects of both virulent NOV strains on chicken splenic lymphocytes and macrophages are further studied and discussed.